COMPARATIVE ANALYSIS OF THE EDUCATIONAL CONCEPTS OF KARL POPPER AND JOHN DEWEY - Gulrukh Azamatova (Modern American Journals, 2025)
The article examines the educational concepts of John Dewey and Karl Popper in a comparative way. The analysis is carried out at the level of epistemological foundations, objectives, didactic methods and political and ethical contexts. Dewey understands education as a process of continuous growth and democratic experience, whereas Popper associates it with the formation of a critical attitude and the maintenance of institutions of an open society. The comparison reveals both differences in the initial assumptions and a common focus on overcoming dogmatism and developing the ability to think critically. The conclusion is made about the complementarity of their approaches and the importance of the ideas of Dewey and Popper for modern pedagogical discussions.
Keywords: Philosophy of education, pragmatism, critical rationalism, experience, democracy, ethics.